ЭРЧИМ ХҮЧНИЙ БОДЛОГЫН ТАЛААРХ ОЛОН УЛСЫН ХАРИЛЦААНЫ ОНОЛ, ҮЗЭЛ ХАНДЛАГА - Ж.ТӨРТОГТОХ; С.Мягмарсүрэн (Politology, 2023)
Nowadays energy has become the essential part of geopolitics and international relations as energy resource and energy security issues dictate international relations and international security agenda. This interdependence has been studied on number of classic theories of international relations. Moreover, not only international relations study but also geopolitical paradigm, security studies have been trying to define world energy policy from their specific angles. However, the most useful theory to study international energy cooperation, energy conflicts and develop alternative scenarios for international energy perspective is fundamental theories of international relations. In particular, realist, liberal, Marxist or radical currents of international relations’ theory have developed their own definition of international energy relations.